Antibacterial activities of oregano essential oils and their active components - Tao, Lei; Liang, Yan; Xia, Zhi; Wang, Xinsheng; Wang, Xiaodong; Chao, Zhe; Guo, Jie (Frontiers in Pharmacology, 2025)
Background: Oregano essential oils (OEOs) and their biological active components are of great interest due to their potent pharmaceutical and antibacterial activities.Methods: OEOs were extracted from wild and cultivated oregano with white or purple flower using our extraction process. We investigated the in vitro antibacterial effects of OEOs and the main active components, carvacrol and thymol. The synergistic effects of carvacrol and thymol were evaluated using checkerboard assay, time-kill assays and systemic infection mice model. The synergistic mechanism was also revealed using scanning electron microscopy (SEM) assay and DAPI/PI staining.Results: Essential oil extracted from wild and cultivated oregano with white flower exhibited potent antibacterial activities against standard strains of Gram-positive and -negative bacteria, with minimum inhibitory concentrations (MICs) range from 0.25-1 mg/mL. The antibacterial activities of carvacrol were obvious higher than that of thymol with MICs values of 0.005-0.04 mg/mL. Carvacrol combining with tobramycin exhibited highly promising synergistic effects (with FICI = 0.25 against E.coli and 0.125 against MRSA) which were further confirmed by the time-kill assays. In the systemic infection mice model, carvacrol combining with tobramycin exhibited potent in vivo antibacterial effects, with significantly improving the survival rate of mice, reducing the MRSA load and alleviating the pathological changes in the lungs of the infected mice. Preliminary explorations for synergistic mechanism suggested that the enhanced antibacterial potential of tobramycin might be attributed to carvacrol with the ability to perforate membrane and induce holes on it.